2015
DOI: 10.1155/2015/756270
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Phytoremediation Potential of Napiergrass Cultivated in Kyushu, Japan

Abstract: Napiergrass (Pennisetum purpureum Schumach), a C 4 tropical species, has been used for forage since it has high dry matter productivity, sustainability over several years in low-altitudinal sites of Kyushu, and little damage from serious pests. Recently, this grass has gained attention due to its potential as a bioethanol feedstock and for phytoremediation. Napiergrass cultivar Wruk Wona was grown as an annual crop in cadmium-(Cd-) contaminated soils under two cutting frequencies. Annual dry matter yield was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Besides rapid growth, an ideal phytoremediator must also possess a high tolerance to the pollutants and the ability to degrade or concentrate high levels of pollutants in its biomass (Buhari et al, 2016). As reported by Ishii et al (2015), P. purpureum can withstand several highly contaminated conditions. Liu et al (2009) and Kang et al (2012) also demonstrated that P. purpureum is resistant to media that are contaminated with heavy metals, including soil with a high copper level in a pot trial and in solutions containing stable caesium.…”
Section: Characteristics Of Pennisetum Purpureum As a Phytoremediatormentioning
confidence: 66%
See 1 more Smart Citation
“…Besides rapid growth, an ideal phytoremediator must also possess a high tolerance to the pollutants and the ability to degrade or concentrate high levels of pollutants in its biomass (Buhari et al, 2016). As reported by Ishii et al (2015), P. purpureum can withstand several highly contaminated conditions. Liu et al (2009) and Kang et al (2012) also demonstrated that P. purpureum is resistant to media that are contaminated with heavy metals, including soil with a high copper level in a pot trial and in solutions containing stable caesium.…”
Section: Characteristics Of Pennisetum Purpureum As a Phytoremediatormentioning
confidence: 66%
“…This is because P. purpureum has the mechanism to tolerate high heavy metal concentrations accumulated in its shoots. For example, from the study by Ishii et al (2015), the cadmium concentration in the soil was reduced by about 4.6% and 2.6% in a single year of P. purpureum cultivation with twice and once cutting, respectively. In addition, cadmiun concentration of 1.47 mg/kg, which is almost equivalent to 15 µM cadmium, in the soil had no observable inhibition on the growth of P. purpureum (Ishii et al, 2015).…”
Section: Phytoextractionmentioning
confidence: 99%
“…(Ni, Cr and Pb) Mining area is always associated with heavy metals that may be contaminated in the surrounding environments (Boom, 2002). Heavy metals can be contaminated with the dust spreading on every surface in the area because of blasting rocks during mining (Bruce et al, 2003;Onder et al, 2007;Gutiérrez-Ginés et al, 2010;Ishii et al, 2015). Heavy metals can also be increased when the soil and grass samples were taken near the shelter mining waste products (Boom, 2002).…”
Section: Chemical Component (Ndf Adf Adl Cellulose and Hemicellulomentioning
confidence: 99%
“…On the other hand, the utilization of post-mine area as a forage crop land is often associated with low-quality grass and so that this study was aimed to evaluate forage quality of the grasses in the mine revegetation area, in addition with the absorption of heavy metals (Ishii et al, 2015). Considerable high content of heavy metal has been reported as a result of several industrial or waste disposal activities in some regions of the world, which could enter to the food chain through different mechanisms and could accumulate in higher organisms such as human beings (WHO, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Napier grass (Pennisetum purpureum Schumach) belongs to a tropical C 4 grass with high dry matter productivity [1,2] and it can elongate its stem internode without phase transition from the vegetative to the reproductive state. Napier grass is now used for multiple purposes, including cut-and-carry fodder for herbivores [3], rotational grazing use [4], and feedstock for bioenergy production [5] and for phytoremediation [6] in the Kyushu area of Japan. Napier grass rarely produces viable seed and thus is commonly propagated vegetatively using stem cuttings and rooted tillers [1,7,8].…”
Section: Introductionmentioning
confidence: 99%